(untitled) (American & British Studies Annual, 2014)
The paper deals with the way the Atlanta Child Murders became the focus of books in different literary genres by James Baldwin, Toni Cade Bambara and Taryaki Jones. Baldwin’s The Evidence of Things Not Seen is a long publicist essay; Bambara used the form of a documentary fictionin Those Bones Are Not My Child, and Jones’ Leaving Atlanta is fiction based on individual memory. The figure of the sorrowing child who illuminates the injustices of the world divided by class, race and wealth is in the center of all three works. Thanks to the figure of the child the tensions and complexities of the adult world become conspicuous; the child acquires the role of a moral model that challenges the mores of American society.